Hurst's the heart update 1 (McGraw-Hill, 1994)
The book discusses the basic concepts of cardiovascular science; describes the pathophysiology, clinical findings and appropriate medical and surgical management of various cardiovascular syndromes ans diseases. Chapter 1 and 2 of this book provide more specific detailed information concerning infarction of the right ventricle and the clinical entity of non-Q-wave myocardial infarction. Chapter 3 provides new material concerning the usefulness of the single-averaged electrocardiogram for detecting patients at hight risk for ventricular tachyarrhythmias and sudden death. In chapter 4, newer and commonly used methods of catheter ablation for the successful treatment of cardiac arrythmias are detailed. Chapter 5 provides extensive information and comparison data on the various types of mechanical and tissue valves used to replace diseased cardiac valves. In chapter 6, considerable important details are given concerning the pathogenesis and pathophysiology of dilated cardiomyopathies, and in chapter 7, recent advances in the management of patients with congestive heart failure are discussed